Key transcriptional regulators of the vasoprotective effects of shear stress - Boon, R. A.; Horrevoets, A. J. G. (Hämostaseologie, 2009)
Atherosclerotic plaque rupture and subsequent thrombosis is the main cause of sudden coronary death. Remarkably, atherosclerosis only develops in certain predisposed areas of the vasculature. Endothelial cells in these predisposed areas experience low or oscillatory shear stress, which activates the proinflammatory and procoagulant transcription factors activator protein 1 (AP-1) and nuclear factor B (NFB), thus inducing a proinflammatory, procoagulant surface. In contrast, healthy endothelial cells that are exposed to prolonged high laminar shear stress, express antiinflammatory and anticoagulant genes. The key shear stress-induced transcription factors that govern the expression of these genes are Krüppel-like factor 2 (KLF2) and nuclear factor erythroid 2-like 2 (Nrf2). Together KLF2 and Nrf2 govern ~70% of the shear stress-elicited gene sets. Nrf2 potently induces anti-inflammatory/antioxidant enzymes, while KLF2 induces anti-inflammatory and anticoagulant proteins, most specifically endothelial Nitric oxide synthase (eNOS) and thrombomodulin (TM). KLF2 also inhibits proinflammatory and antifibrinolytic genes through inhibition of the proinflammatory transcription factors AP-1 and NFB. The widespread beneficial effects of the key transcription factors KLF2 and Nrf2 on endothelial phenotype, holds the promise that their targeted modulation might lead to a new class of cardiovascular drugs.
Keywords: Shear stress; transcription factor; KLF2; Nrf2